Gender Differences in Cooperation in the U.S. Congress? An Extension of Gagliarducci and Paserman (2022) - Manuel Bagues; Pamela Campa; Giulian Etingin-Frati (Institute for Replication (I4R), 2023)
Gagliarducci and Paserman (2022) study gender differences in cooperative behavior among politicians using information from the U.S. House of Representatives between 1988 and 2010 on (i) the number of co-sponsors on bills and (ii) the share of co-sponsors from the rival party. Through different empirical strategies, they show that women-sponsored bills tend to have more co-sponsors, but the gap is only statistically significant among Republicans. Moreover, Republican women recruit a significantly larger share of co-sponsors from the rival party than Republican men, whereas the opposite is true among Democrats. GP argue that the observed pattern is consistent with a commonality of interest driving cooperation, rather than gender per se, since during this period Republican women were ideologically closer to the rival party than their male colleagues, while female Democrats were further away. We examine the robustness of these findings to (i) the correction of some errors in two control variables of the dataset used by GP and (ii) clustering the standard errors at the individual level, instead of individual-term. These changes have a relatively minor impact on results: most coefficients are still statistically significant and the main conclusions from the analysis are confirmed. Furthermore, we extend the analysis to the 2011-2020 period. The analysis of gender differences in bipartisan cooperation confirms GP's hypothesis that ideological distance plays an important role. However, results are slightly different when we analyze overall cooperation. The gender gap in favor of women is larger in magnitude than in GP and it is statistically significant in several specifications, providing support for the hypothesis that gender also matters for cooperation.
Keywords: 330